Süddeutschland: Siedlungsbestattungen der Hallstatt- und Frühlatènezeit - Müller-Scheeßel, Nils (e-Forschungsberichte des DAI, 2023)
The project, funded by the German Research Council from 2010 to 2013, dealt with settlement burials of the Early Iron Age in south and southwest Germany. It set out to provide answers to the phenomenon that human corpses were deposited in settlement pits in apparently casual ways. The most likely explanation from archaeological observations and the results of isotope analyses seems to be a belief in „untimely“ deaths these individuals had suffered.